Big-O Test of RSA Algorithm Complexity in Civil DataBase ( SIN / eID ) (International Journal of Engineering and Computer Science, 2015)
Analysis of Algorithms is the area of computer science that provides tools to analyze the efficiency of different methods ofsolutions. The time efficiency of the algorithms can be characterized by growth rate functions ( Big-O ).Big-O represents how fast does an algorithm grow with respect to N number of steps. The algorithm that will be discussed are taken fromcomputer programs that implemented the RSA Encryption in a Single Identification Number (SIN) or the e-ID CARDS in Indonesia whichis a unique identification number that is integrated with the combined data from a variety of government agencies and private sector. RSAEncryption program used to maintain the security and confidentiality of messages, data, or information in a computer network, so that cannot be read or understood by just anyone. In this paper, the authors analyze the proper cryptographic system application applied to theintegrated data base in SIN (e-ID). Scoring algorithm is based on: execution time (from the most dominant functions), memoryusage/resources, the simplicity and clarity of the algorithm. The steps of analysis algorithms developed by specifying a type/nature of theinput data, measuring the execution time (Running Time) of each function, analyze mathematically with the data test Big-O with graphs andtables of Polynomial to determine its average case.